Noise generated by a moving line source in a dissipative atmosphere - R. MAKAREWICZ (Archives of Acoustics)
It is the purpose of this paper to present the resultant effect of geometrical spreading, air absorption, Doppler frequency shift and the distortion of the sound field due to the motion of a line source. It is assumed that the source is moving slowly along a straight line. The results obtained can be used for prediction of the A-weighed sound pressure level of railway noise.